POTENSI AKTIVITAS ANTIOKSIDAN METABOLIT SEKUNDER DARI BAKTERI ENDOFIT PADA DAUN Moringa oleifera L - Susi Juni Yati; Sumpono Sumpono; I Nyoman Candra (University of Bengkulu, 2018)
[POTENTIAL ANTIOXIDANT ACTIVITY OF SECONDARY METABOLITES FROM ENDOPHYTE BACTERIA ON Moringa oleifera L LEAF] This research aims to know the similarities between secondary compound metabolites produced by endophyte bacterial on host leaves and from Moringa oleifera L (kelor) leaves as well as determine the magnitude of antioxidant activity compounds of secondary metabolites produced by bacterial endophyte. Based on the results of the test compound is secondary metabolite in both samples, for secondary metabolite compounds in the extract of the leaves of M. oleifera L. contains identified steroid compounds, flavonoids, saponins, tannins and phenolic compounds, while for metabolites secondary bacterial endophyte undetectable on the existence of any secondary metabolite compounds.For testing of antioxidants on endophyte bacterial extracts of leaves of M. oleifera L is done using the DPPH method, performed on variations of the concentration of 200, 400, 600, 800, and 1000 ppm with Ascorbic acid as a comparison. The results of the test get an IC50 of M. oleifera L leaf extract at 243.67 ppm, and supernatan extract from endophyte bacterial at 492 ppm. The IC50 values showed antioxidant activity in secondary metabolite compounds derived from extracts of the leaves of M. oleifera L which has an extreme antioxidant category. The amount of antioxidant activity for secondary metabolite compound extracts of bacterial endophyte on leaves of M. oleifera L category is feeble, and to extract the supernatan activity is weak compared to the value of the antioxidant activity of Ascorbic acid.